Pengaruh Citra Merek, Periklanan dan Persepsi terhadap Minat Menabung Nasabah Tabungan Mabrur di bank Syariah Mandiri KCP Rancaekek - Dwiki Astuti; Dadang Dimyati; Haekal Pirous (Jurnal Dimamu, 2022)
Based on observations, that the background of this research is the fluctuating number of mabrur savings customers, where there are many factors that influence the development of the number of mabrur savings customers at Bank Syariah Mandiri Rancaekek Sub-Branch Office. This study aims to determine how the influence of brand image, advertising and perception on the interest in saving savings simultaneously at Bank Syariah Mandiri KCP Rancaekek. The object of the research is the mabrur savings customer at Bank Syariah Mandiri KCP Rancaekek. The type of research is quantitative associative, with primary data types and data collection in the form of observations, interviews, questionnaires and literature studies. While the sampling technique using non-probability sampling with the type of sample is Incidental sampling. The population is all mabrur savings customers at Bank Syariah Mandiri, totaling 712 people with a sample of 88 people. The results of the study that there is an influence of brand image on the interest in saving savings seen from the results of the analysis of the coefficient of determination with an R square value of 42.4%, there is an influence on the influence of customer deposits with an R square value of 38.3%, there is a perception of customer savings interest with the value of R square is 36.2%. There is a simultaneous influence between branding, advertising and perceptions of interest in saving for mabrur savings at BSM KCP Rancaekek seen from the analysis of the coefficient of determination with an R square value of 49.3%.